An optimality analysis of Malay loanwords in Japanese - Aznur Aisyah,; Zaharani Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2017)
This study aimed to examine and explain the phonology of Malay loanwords in Japanese using Optimality Theory. The analysis was based on secondary data extracted from the Senyum magazine published in Malaysia that utilises Japanese language in its writing. The relevant data which was selected manually, was then analysed and explained using a constraints-based approach of Optimality Theory. This article focuses on vowel lengthening and epenthesis repair strategies that occur during the borrowing process from Malay to Japanese. The vowel lengthening repair strategy followed by vowel epenthesis are evoked from the syllable structure of Japanese, particularly the coda condition. The word that ends with /CVC/ (Consonant+ar/or/ur) will be changed to /CV:CV/ (Consonant+ a:ɾɯ/ o:ɾɯ/ ɯ:ɾɯ). This kind of loanword adaptation process will undergo vowel lengthening and the coda consonant will resyllabified as an onset of the following syllable. This study has suggested a set of markedness and faithfulness constraints that are hierarchically ranked in the grammar. The interaction between the constraints has successfully been accounted for the phonology of loanword adaptation in Japanese. The increase in the number of Japanese in Malaysia since the implementation of Malaysia My Second Home programme has led to a wider exposure of Malay words to the Japanese. Therefore, this research will not only benefit linguists, it will also enhance the Malaysian society’s understanding of Japanese pronunciation as it differs from the Malay phonology. It will help to eliminate the confusion that may occur during conversation between Japanese and Malays and vice versa.